Fiesta space: La Plaza Nueva - Segura Moneo, Julio (Huarte de San Juan. Geografía e Historia, 2011)
It was Designed and built in 1687 outside the walls of the city to celebrate festivities, Specially bullfighting fair. It was built on the river Queiles near its confluence with the River Ebro and the river Vencerol –which makes it unique in its style–, and high-risk of flooding. It was a great technical impact, as can be seen in the construction process, in addition to constitute in a short period of time, the whole of bullring, slaughter and butcher. Besides, it opens the expanse of the city to new spaces. Outdated its role as bullring, it is nowadays the meeting point between the inhabitants, residents, and Tourists to celebrate the important events.
Keywords: Civil architecture; public squares; bullring; urbanism; artistic heritage